Disain SPWM Multilevel Inverter Satu Fasa 15 Level Dengan menggunakan Kendali Arus PLN - Effendi; Rachmad Ikhsan (J-Innovation, 2020)
The fifteen level single phase Multilevel Inverter (MLI) in this research is constructed by using three independent DC sources in form of 12, 24, and 48 Volts batteries which arranged in series where each source separated by MOSFET that used as switch and uses three diodes and furthermore connected with H-Bridge circuits which serves to reverse the direction of the electric current to producing alternating current on the resistif load. MOSFET switching circuit is designed by using Sinusoidal Pulse Width Modulation (SPWM) methode which using AC PLN current as control reference system, by using the operational amplifier component that used as comparator between the reference wave with carrier voltage from DC sources as many as sevens where use analog and digital electronic components which function to activate the gate of each MOSFET in the power circuits. By using combination of voltage arrangement battery this MLI can produce an output wave not much different from previous research that is equal to 15 levels, THD of 5.6%, and frequency of 50 Hz but the number of switches, diodes and carrier voltages used is less than previous researches.